AN OBSERVATIONAL STUDY DEMONSTARTING THE MEASUREMENT, CHARACTERIZATION AND VALIDATION OF EXPRESSIONS OF CALPROTECTIN IN HUMAN SWEAT THROUGH A SWEAT WEARABLE. (26th January 2023) - Prasad, Shalini; Jagannath, Badrinath; Lin, Kai-chun; Muthukumar, Sriram; Shahub, Sarah; Sardesai, Abha
Abstract: BACKGROUND: Inflammatory bowel diseases (IBD) comprising Crohn's disease (CD) and ulcerative colitis (UC) are typically characterized by chronic episodes of inflammation within and through the gastrointestinal (GI) tract. In many inflammatory conditions including IBD, Calprotectin (CP) is well-studied (systemic and fecal) and employed by clinicians due to assay stability and low cost to effectively guide diagnostic and therapeutic decisions. While, accessing fecal CP is non-invasive, there is significant resistance to continuous fecal CP testing from patient-use and patient enablement aspects due to the challenges is sample collection, hence there is a current unmet need to access CP in a completely non-invasive manner. METHODS: The sweat sensor device and reference ELISA was used to investigate and quantify CP levels in sweat. The immunoassay on the sweat sensor was developed by immobilizing specific capture probe antibody to capture CP in sweat. The sensor response was measured using impedance spectroscopy. Sweat samples from seven healthy and one IBD subject were collected and correlation analysis between the sweat sensor device and ELISA was performed to evaluate CP levels in sweat. RESULTS: The sweat sensor device demonstrated a wide dynamic range of 0.1- 10 μg/mL with a limit of detection of 0.1 μg/mL. The sensor was also specific to CP and demonstrated negligible to no response for non-specific inflammatory markers such as C-reactive protein, interleukin-6. Excellent correlation was achieved between ELISA and the sweat sensor device with Pearson's r>0.95. Human subject studies demonstrated that elevated basal levels in IBD subject (500 ng/mL) as compared to healthy cohort ( 350 ng/mL). Further, 3 times increase in CP levels was observed due to flare-up in the IBD subject with a mean concentration 1300 ng/mL as compared to the basal levels. CONCLUSION: This work is the first demonstration of CP in sweat. The pre-clinical results of elevated CP levels will be of significant interest to clinicians as it provides a non-invasive and non-intrusive tracking flare-ups in IBD patients and can aid in better management of the disease.